Preoperative practice of surgical position reduces postoperative pain and discomfort in patients receiving kidney surgeries: a nonrandomized pilot study - Huang J; Zhang D; Li SJ; Xi Y; Cui LY; Gao FL (Dove Medical Press, 2018)
Jing Huang,1 Dan Zhang,2 Shu-Jing Li,1 Ying Xi,1 Li-Yan Cui,1 Feng-Li Gao3 1Department of Urology, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Department of Nephrology, Beijing, Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of China; 3Department of Nursing, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of China Objective: Prolonged maintenance of surgical position often results in postoperative pain and discomfort in patients. The present study aimed to investigate the effect of preoperative practice of surgical position on postoperative pain and general comfort in patients receiving kidney surgeries. Methods: For this nonrandomized pilot study, 74 patients receiving kidney surgeries were selected using the probability sampling method. Patients from ward 1 were assigned to the practice group (n=35), and those from ward 2 were assigned to the control group (n=39). The practice group were instructed to practice the surgical position for 3 days prior to the surgery. Postoperative pain and comfort were surveyed using two questionnaires for 3 days, respectively. The postoperative pain scores were compared using the Student’s t-test. Results: The two groups did not differ significantly in wound pain on postoperative days 1–3 (P > 0.05). However, the practice group showed significantly reduced low back pain and contralateral shoulder pain than the control group for 3 postoperative days (P < 0.05). The physical domain score was significantly higher in the practice group than in the control group (P < 0.01). Conclusion: Preoperative practice of surgical position can effectively reduce postoperative low back pain and contralateral shoulder pain in patients receiving kidney surgeries and improve the physical comfort. Keywords: surgical position, kidney surgery, postoperative pain, comfort, low back pain, physical comfort